Участие Советского Союза в программах библиотечной деятельности ЮНЕСRО - Мацявичюте, Эляна (Knygotyra, 1991)
The Soviet Union became the member of UNESCO in 1954. Since then the influence of socialist countries became much more noticeable in UNESCO. It was felt in the field of librarianship as well. The librarians from the USSR took part in most international meetings organized by this organization. They worked at creating the UNISIST and NATIS programmes. The main principles of soviet librarianship prevail in the concept of NATIS. The seminars for the librarians from developing countries held in Moscow – Tashkent – Alama-Ata (1972 and 1974) were very successful. The national libraries of socialist countries study various problems of library work for UNESCO under the leadership of the USSR Lenin State Library. However there are some shortcomings in cooperation between UNESCO and Soviet librarians. Many possiblities are not used up by USSR and the Organization.